Análise da sustentabilidade econômica, social e ambiental do cultivo orgânico de hortaliças: o caso dos produtores da Associação para o Desenvolvimento da Agropecuária Orgânica - ADAO - Mesquita Filho, João Benigno de (2006)
This research analyzes the experience of the production of organic hortalics in the city of Guaraciaba do Norte-CE, project carried through for the Association for the Farming Development of Organic- the ADAO, as alternative to the conventional culture. The obejective of the work is to analyze the economic, social and ambient sustentabilidade of the agriculturists who produce in the organic system. So that this was possible, an index of sustainable development was used (IDS) that he is composed for three other points, a pointer of Economic Performance (IDE), a pointer of Desempenho Social(IDHA), and a pointer of Ambient Performance(IDA). These pointers has shown that the organic culture is better inserted in the aspects os the sustentabilidade. The IDS got a average of 0,600. The shunting line standard is of 0,265 what it indicates that agriculturits in this type of culture inserted in a level of high development exist. The index of ambient development which had the use of the agroecologycs principles in the activity, presented a average of 0,800 with shunting line standard of 0,447. The social performance represented by the IDHA, presented an average performance of 0,524 with shunting line standard of 0,381. The index economic perfromance got the lower average performance of the three pointers with 0,447 of average and shunting line high standard of 0,476. The work concludes then that the organic culture is advantageous for causing one better quality of life to that they exert this activity.